Pengaruh Metode Kombinasi Bayt Tamyiz dan Amtsilati dalam Meningkatkan Kemampuan Membaca Kitab Kuning Santri di Pondok Pesantren Al-Mushlih Teluk Jambe Timur Karawang - Putri, Karina Shintia; Darmiyanti, Astuti; Fahmi, Yadi (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
Islamic education is a purposeful and planned effort to train students to have faith, knowledge and charity at the same time, as well as physical and spiritual balance in the book, therefore, Islamic religious education focuses on helping students develop personalities that meet Islamic standards through physical guidance. and Spiritual. The aim of this research is to determine the effect of the Bayt Tamyiz and Amtsilati Combination Method in improving the reading ability of the yellow book of students at the Al-Mushlih Islamic Boarding School in Teluk Jambe Timur Karawang. This research method uses a quantitative approach. The population in this research is the total number of students at Pondok Persantrern Al-Murshlih Terlurk Jamber Timur Karawang which consists of 230 male and female students, with a sample of 58 students. The data analysis used is descriptive analysis with validity tests and classical assumption tests. Testing is assisted by the SPSS tool. The research results show that the combination method of bayt tamyiz and amtsilati has a significant impact on the ability to read the Islamic boarding school of Islamic boarding school students at the Al-Murshlih Terlurk Jamber Timur Karawang Islamic boarding school.